2013
DOI: 10.3390/en6094639
|View full text |Cite
|
Sign up to set email alerts
|

Towards Energy Efficiency: Forecasting Indoor Temperature via Multivariate Analysis

Abstract: Abstract:The small medium large system (SMLsystem) is a house built at the Universidad CEU Cardenal Herrera (CEU-UCH) for participation in the Solar Decathlon 2013 competition. Several technologies have been integrated to reduce power consumption. One of these is a forecasting system based on artificial neural networks (ANNs), which is able to predict indoor temperature in the near future using captured data by a complex monitoring system as the input. A study of the impact on forecasting performance of differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…Input signal sequence is sampled at one minute period (indoor temperature time series task presented at [34]), and pre-processed by a low-pass filter to get the mean value of the current plus last 14 samples, introducing a delay of 7 minutes in the predicted values. Hence, s 1 s 2 ... s N are computed, where…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Input signal sequence is sampled at one minute period (indoor temperature time series task presented at [34]), and pre-processed by a low-pass filter to get the mean value of the current plus last 14 samples, introducing a delay of 7 minutes in the predicted values. Hence, s 1 s 2 ... s N are computed, where…”
Section: Data Descriptionmentioning
confidence: 99%
“…Usually, statistical methods are used to estimate the weight parameters of these models. ANNs have been widely applied to this task [35,2,34], normally trained by one of the different variants of Gradient Descent (GD) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The computer based system modified the velocity of the ventilation fans according to the environmental temperature; for example for temperatures of 10 °C and 38 °C the used fan speeds were 1.7 m/s and 5.5 m/s, respectively [15]. Zamora-Martínez et al [16] described an indoor temperature forecasting system based on artificial neural networks. The system utilized various sensors inputs, including CO 2, humidity and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The system utilized various sensors inputs, including CO 2, humidity and temperature. As the preliminary tests showed that maintaining the current temperature used only 30%-38.9% of the energy needed to lower the temperature, an accurate forecasting of the indoor temperature could be exploited in energy efficient control of the indoor conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Models based on physical principles can vary largely from extremely complex to more simplified structures with respect to the number of parameters and variables [14][15][16][17] but they usually need detailed information on the building characteristics and are in general too computationally heavy to be effectively used for control purposes. On the other hand, data driven models [18][19][20][21][22][23][24][25][26][27][28] are based solely on measurements and are typically identified without information on the physical nature of the building properties. Hybrid or grey box models are a combination of data driven and physical modelling approaches [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%